Analisis Brand Attachment dan Brand Love dalam Meningkatkan Brand Loyalty Studi Merek pada Havaianas - Achmad Arifin; Apriyana, Nurliya (JURNAL MANAJEMEN MOTIVASI, 2026)
In the fashion lifestyle industry, emotional connections with consumers have become increasingly important in fostering brand loyalty. This study aims to examine the influence of brand attachment and brand love on brand loyalty among Havaianas consumers. A quantitative survey was conducted involving 108 respondents selected through purposive sampling. Data were analyzed using multiple linear regression with SPSS. The results indicate that both brand attachment and brand love have positive and significant effects on brand loyalty, with brand love showing a stronger influence. The findings imply that companies should strengthen consumers’ emotional experiences to enhance long-term brand loyalty.